Scaling Up the Service Innovation Fund Projects of Access to Information (A2i) Program of Bangladesh: The Way Forward for Private Innovators (Global Journal of Management and Business Research, 2018)
The Access to Information (A2i) Program is a flagship project under the Prime Minister#x2019;s Office and jointly financed by UNDP, USAID and the Government of the People#x2019;s Republic of Bangladesh to support the Vision 2021, through promoting and integrating digitization in governmental activities and through innovation in service delivery. One of the core components of the project is the Service Innovation Fund, managed by the Innovation Team, which provides seed money to innovators of up to Tk. 2.5 million for carrying out pilot projects of a new product or service. After piloting, the ownership of some suitable projects is taken up by the government and the associated service is incorporated into the relevant Ministry or Department. For the rest of the projects, the innovators need to commercialize the venture on their own. Most innovators do not have the capacity to mass produce, and lack the business acumen to create sustainable business models which would attract private investment. This study has tried to suggest a solution to this problem. The study recommends that A2i get involved in a greater scale to provide necessary grooming and mentorship to the projects from the very beginning to address issues as piloting progresses. The grooming workshops should be inclusive of all applicants of the innovation fund before any stage of screening is conducted to disseminate basic business knowledge among a larger group of innovators. Involving representatives from the business community with the projects would aid in better business development and may help secure private funding easily.
Keywords: A2i; service innovation fund